Cardiorespiratory adaptation to sport in young school boys - G. S. Senatorova; O. L. Onikiienko (Journal of Education, Health and Sport, 2018)
There is insufficient number of researches dedicated to cardiorespiratory adaptation in various physical activities in general, and especially in children and adolescents for certain types of sport.